Corruption Case Analysis on PT. ASABRI: Ethical Problem or Governance Failure? - Bryan Habib Gautama,; Debby Chyntia Putri,; Faisal Akbar Haris,; Subagio, (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This study aims to determine issues of ethics and corporate governance that occurred in the corruption case of PT. ASABRI. This research used is a qualitative approach with literature study. Corruption case of PT. ASABRI occurred as a result of the company management agreement with outsiders to manage the company's investment. Based on the chronology, there are ethical issues in decision making and poor company management. There are several solutions that can be taken such as building a corporate culture, implementing Good Corporate Governance guidelines, and implementing a comprehensive risk management system and internal control system.